NEW RESEARCH IN HUAYURCO: INITIAL RESULTS OF THE EXCAVATIONS IN A SITE OF CLOUD FOREST FROM THE PERUVIAN ANDES - Clasby, Ryan (2012)
Discovered in 1961 by Pedro Rojas (1961, 1985) as part of follow-up research to Tello’s Marañon expedition, Huayurco was one of the first sites in the eastern Peruvian Andes to be formally excavated. The recovery of exotic offerings in addition to multiple finely crafted stone bowls led Rojas and Donald Lathrap (1970: 108-109) to suggest that Huayurco was an important center of exchange during the Early Horizon (900-200 B.C), helping to facilitate interregional interaction between the Pacific coast, highlands and Amazonian lowlands. In 2010, we conducted excavations at Huayurco to examine this hypothesis. Preliminary survey and excavation results confirm Huayurco’s long distance relationships and show that the site is much larger than originally recorded with a long and complex occupational history.